Evaluation of Ziziphus abbysinica fruit paste as used by the pastoral community of West Pokot, Kenya for the preservation of fresh pork sausages - Onyango, C. A.; Nyaberi, M. O.; Mathooko, F. M.; Maina, J. M.; Makobe, M.; Mwaura, F. (My University, 2012)
The pastoralists from West Pokot district have used the fruit paste of Ziziphus abyssinica A. Rich (AZA), to process and preserve meat over a long period of Time. This study tests the effectiveness the herb to preserve meat using pork sausages. The effectiveness of AZA was tested by incorporating the aqueous extracts of the fruit paste of this herb, into samples of pork sausages stored at both 4ºC and 25ºC. Total viable count (TVC), Staphylococcus aureus counts, Escherichia coli plate counts, TVB-N and rancidity tests were undertaken over a period of 14 days. At 4ºC the samples preserved with AZA at the rate of 3.1mg/g of meat attained the total viable count (TVC) upper limit of 6 log cfu/g in about 10 days, and the TBARS value maintained below 0.9mgMA/kg during the same period. On the eleventh day at 4 ± 2°C the total volatile base nitrogen values of sausages treated with AZA herbs and sodium metabisulphite were 11.5 and 16.1mg/100g respectively. This may lead to the conclusion that AZA has higher antioxidant properties than sodium metabisulphite, while the latter has better antimicrobial properties than AZA. Further research on quantitative and qualitative analysis of the phytochemicals incorporating AZA should be developed.